High-density immobilization of a ginsenoside-transforming β-glucosidase for enhanced food-grade production of minor ginsenosides - Cui, Chang-hao (Appl Microbiol Biotechnol, 2019)
Use of recombinant glycosidases is a promising approach for the production of minor ginsenosides, e.g., Compound K (CK) and F(1), which have potential applications in the food industry. However, application of these recombinant enzymes for food-grade preparation of minor ginsenosides are limited by the lack of suitable expression hosts and low productivity. In this study, Corynebacterium glutamicum ATCC13032, a GRAS strain that has been used extensively for the industrial-grade production of additives for foodstuffs, was employed to express a novel β-glucosidase (MT619) from Microbacterium testaceum ATCC 15829 with high ginsenoside-transforming activity. A cellulose-binding module was additionally fused to the N-terminus of MT619 for immobilization on cellulose, which is an abundant and safe material. Via one-step immobilization, the fusion protein in cell lysates was efficiently immobilized on regenerated amorphous cellulose at a high density (maximum 984 mg/g cellulose), increasing the enzyme concentration by 286-fold. The concentrated and immobilized enzyme showed strong conversion activities against protopanaxadiol- and protopanaxatriol-type ginsenosides for the production of CK and F(1). Using gram-scale ginseng extracts as substrates, the immobilized enzyme produced 7.59 g/L CK and 9.42 g/L F(1) in 24 h. To the best of our knowledge, these are the highest reported product concentrations of CK and F(1), and this is the first time that a recombinant enzyme has been immobilized on cellulose for the preparation of minor ginsenosides. This safe, convenient, and efficient production method could also be effectively exploited in the preparation of food-processing recombinant enzymes in the pharmaceutical, functional food, and cosmetics industries. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00253-019-09951-4) contains supplementary material, which is available to authorized users.